Model Pemidanaan Berbasis Nilai Kerugian Ekonomi dalam Aksi Filantropi Crowdfunding - Saravistha, Deli Bunga; Surya Mataram, I Nyoman Gede (Jurnal Penelitian Hukum De Jure, 2025)
Crowdfunding, have become increasingly popular since the onset of the Covid era and have become a new social phenomenon until now. This is marked by the emergence of various donation collection platforms in Indonesia, making Indonesia the most generous country according to the Charities Aid Foundation World Giving Index 2021 survey. The regulation that serves as the basis for this activity is Law Number 9 of 1961 and Government Regulation Number 29 of 1980. Numerous cases with various methods of operation have begun to surface; however, regrettably, they fall short of the community's expectations, particularly those of well-meaning donors who are concerned about humanitarian issues. This study aims to create a more effective legal regulatory model by examining situations from a new perspective that incorporates economic characteristics. The subjects of this research are crowdfunding actors, donors, and other related parties.. The research method used is the normative research method with the help of Responsive Law Theory as an analytical tool. With a punishment model based on the value of economic loss and also implemented based on the principle of restorative justice, the research findings provide a more responsive resolution mechanism that does not undermine the authority of criminal law and views the legal system as not immune to the influence of other subsystems, including the economic subsystem. It is suggested that laws that are no longer effective in reaching social media-based crowdfunding patterns which not only spread swiftly but may also transcend national boundaries be renewed.